Determinasi Kualitas Pelayanan Puskesmas, Kepercayaan, dan Kepuasan Pasien Terhadap Loyalitas Pasien Puskesmas Merdeka Bogor - Nurinsan, Nurinsan; Renea, Aminda Shinta; Asri, Arsyati Masitha (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2023)
This study aims to determine the effect of health center service quality and trust on patient loyalty through patient satisfaction. The type of research used is quantitative. The research scale used in this study is the Likert scale. The population in this study was the number of patients at the Merdeka Bogor Health Center in the last three years, totaling 114,753 patients. Data analysis techniques using SPSS 23.0 and path analysis. The results showed that the quality of puskesmas services had a positive and significant effect on patient satisfaction at the Merdeka Community Health Center, Bogor City. Patient trust has a positive and significant effect on patient satisfaction at Merdeka Community Health Center, Bogor City. The quality of puskesmas services has a positive and significant effect on patient loyalty at the Merdeka Health Center, Bogor City. Patient trust has a positive and significant effect on patient loyalty at Merdeka Community Health Center, Bogor City. Patient satisfaction has a positive and significant effect on patient loyalty at Merdeka Health Center, Bogor City. Health center service quality has a positive and significant effect on patient loyalty mediated by patient satisfaction at the Merdeka Health Center in Bogor City. Patient trust has a positive and significant effect on patient loyalty mediated by patient satisfaction at Merdeka Health Center, Bogor City